Marine Propulsors - Sverre Steen (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book provides an update on the state of the art of hydrodynamic aspects of marine propellers and turbines, covering predictions using numerical and experimental methods, where the numerical methods comprise both potential flow panel methods, Navier-Stokes solvers and mixed methods. Open and ducted propellers, as well as azimuthing thrusters are represented, as well as operation in steady conditions, waves and off-design conditions. The book consists of 16 peer-reviewed scientific papers previously published in Journal of Marine Science and Engineering.